Oxygen saturation improved with nitrate-based nutritional formula in patients with COVID-19. Issue 4 (April 2021) - Ostojic, Sergej M.; Milovancev, Aleksandra; Drid, Patrik; Nikolaidis, Alexandros
In this open-label case series trial, we evaluated the effects of a nitrate-based nutritional formula on oxygen saturation (SpO2 ) and patient-reported outcomes in individuals with coronavirus disease 2019 (COVID-19). Five adult patients (three men and two women, age 39.6 ± 6.9 years) with a positive COVID-19 test result, breathing difficulties, and SpO2 ≤95%, who were free from other pulmonary and cardiovascular conditions, were recruited for this study. Participants were assigned to receive a multi-component nutritional formula (containing 1200 mg of potassium nitrate, 200 mg of magnesium, 50 mg of zinc, and 1000 mg of citric acid) every 4 hours during the 48-hour monitoring period. In all participants, SpO2 improved immediately after administration of the nutritional formula, from 1 to 7 percentage points (mean increase 3.6 ± 2.7 points; 95% confidence interval 0.3 to 7.0). SpO2 remained above baseline values throughout the monitoring interval, with values persisting over threshold values (>92%) for all patients and at each time point during the 48 hours. No patients reported any side effects of the intervention. These promising and rather unexpected results call for immediate, well-sampled, mechanistic randomized controlled trials to validate our findings.